Combined observations of Arctic sea ice with near‐coincident colocated X‐band, C‐band, and L‐band SAR satellite remote sensing and helicopter‐borne measurements. Issue 1 (28th January 2017) - Johansson, A. M.; King, J. A.; Doulgeris, A. P.; Gerland, S.; Singha, S.; Spreen, G.; Busche, T.
Abstract: In this study, we compare colocated near‐coincident X‐, C‐, and L‐band fully polarimetry SAR satellite images with helicopter‐borne ice thickness measurements acquired during the Norwegian Young sea ICE 2015 (N‐ICE2015) expedition in the region of the Arctic Ocean north of Svalbard in April 2015. The air‐borne surveys provide near‐coincident snow plus ice thickness, surface roughness data, and photographs. This unique data set allows us to investigate how the different frequencies can complement one another for sea ice studies, but also to raise awareness of limitations. X‐band and L‐band satellite scenes were shown to be a useful complement to the standard SAR frequency for sea ice monitoring (C‐band) for lead ice and newly formed sea ice identification. This may be in part be due to the frequency but also the high spatial resolution of these sensors. We found a relatively low correlation between snow plus ice thickness and surface roughness. Therefore, in our dataset ice thickness cannot directly be observed by SAR which has important implications for operational ice charting based on automatic segmentation. Key Points: Three different synthetic aperture radar (SAR) frequency bands are compared regarding their response to different sea‐ice characteristics Newly formed sea ice generate an above average response in L‐band and below average response in C‐band and X‐band copolarization ratio Surface roughness and snow pack structure can in some cases be a stronger influence on sea ice classification than sea‐ice thickness itself